Realidade, comoção e catarse: a função dos recursos dramáticos no docudrama televisivo ‘Por toda minha vida’ - Santos, Débora Laís Ferraz dos (2015)
This thesis aims to investigate the re-elaboration of the modern melodrama in the TV show All my life _ and the implications that result from its docudrama form (by definition, a form that combines two different traditions with different spectatorial pacts). The hypothesis is that, contrary to what is advertised, the documentary (the testimonies, uses of archival material and, homemade videos) serves as mere support for fiction and thus collaborates with the melodramatic elaboration, provides a real seal for history and enhances the emotion of the viewer. Considering the plot and form through the prism of Imagination melodramatic founded by Peter Brooks, the idea is to approach the object of study combining the analysis plane by plane with a structural analysis of post-script of the episodes.